PEMBERDAYAAN TOUR GUIDE EKOTURISME DI KAWASAN CAGAR BUDAYA DANAU TAMBLINGAN-BATUKARU BALI - Wardi, I Nyoman (Bumi Lestari, 2013)
Abstract Training Ecotourism Tour Guide Batukaru Heritage Region-Lake Tamblingan performed at Munduk Buleleng on 1 until 7 September 2012. The community service was held in SD 3 hall Tamblingan and the meeting was attended by 20 participants from organisation guide (OBB) including the head of OBB (Organisasi Bangkit Bersama). The aims of this training to enhance the knowledge and skills as a tracking tour guide in Batukaru-Tamblingan. Training is also intended to provide a briefing on the knowledge ecosystem of lakes, forest and about the history and function of the cultural heritage in the region Batukaru- Tamblingan which now has been declared by UNESCO as a World Cultural Landscape in Bali. As a local tour guide, which is still weak foreign language skills, age, and education level of the participants is quite heterogeneous effect on the rate of absorption ability and spirit training. Ecotourism tour guide training is expected to re-integrate the social cohesion and sustainable society in harmony. Recognizing the heterogenity of the condition of the trainee, techniques and methods of presentation of training materials, must be adapted to the conditions so that the material can be absorbed optimal. The first material was delivered in a lecture and presented by using the Microsoft Power Point program and discussion to increase participants interest on the topic. Second, the practice of direct methods on objects that exist in the empirical Tamblingan Munduk Village. The practice of tour guide in the field for two days with short track and medium tract. Based on the evaluation performed the training process, and from the impressions and messages conveyed by the trainees at the time of closing, was satisfied and happy training. A participants gave very enthusiastic responses and are expected to continue to be the quality of human resources and OBB members of the community can be improved.
Keywords: Keywords: ecosystem, cultural heritage, cultural landscape, ecotourism tour guide